PENGARUH PRODUK, HARGA, DAN DISTRIBUSI TERHADAP KEPUTUSAN PEMBELIAN KUE BANGKIT SYEMPANA DI KOTA PEKANBARU RIAU - Resti Fitriani; Yunia Wardi (Jurnal Riset Manajemen Bisnis dan Publik, 2014)
This study aims to determine the effect of the variables of product, price , and distribution to the purchasing decision Syempana cake rise in the city of Pekanbaru and specifically to determine ( 1 ) The effect of the product on purchase decision , ( 2 ) The effect of price on purchase decisions ( 3 ) Effect of distribution to the purchasing decision . This research is a descriptive study . The population in this study are all potential consumers Syempana cake rise in the city of Pekanbaru . The sampling technique was accidental sampling with a sample size of 100 people . The technique of data analysis using logistic regression analysis . The results showed that ( 1 ) Product significant effect on purchasing decisions , ( 2 ) price significantly influence purchase decisions , and ( 3 ) distribution significantly influence purchasing decisions . The survey results revealed that the variable product gives a greater influence on purchase decisions Syempana cake rise . Results of logistic regression a significant difference between the independent variables ( product , price , and distribution ) to the buying decision for 25.396. Keyword : purchase decisions, product, price, distribution